Comparative Study between Primary Closure and T-tube Drainage after Open Choledochotomy - Asaduzzaman, Md; Mia, Md Golam Mostofa; Abdullah, SM; Islam, Md Shofiqul; Hanif, Mohammad Abu; Karim, SM Rejaul (Medicine Today, 2017)
Common Bile Duct (CBD) exploration for choledocholithiasis is usually closed after T-tube insertion. However, complications of T-tube insertion limit its use. In the present study, we wanted to compare outcomes between primary repair of choledochotomy and traditional T-tube insertion. Thirty patients with CBD stones admitted at Tangail Medical College Hospital, Tangail, from January 2010 to December 2015, were included in this study. The patients were randomly divided into two groups: T-tube drainage group and primary closure group. Intraoperative findings and postoperative complications were recorded and analyzed. There was no mortality and retained stones in both groups. Two of 15 patients in the Ttube group and four of 15 patients in primary closure group suffered from minor bile leakage. There was no major bile leakage in the T-tube group but one patient in the primary closure group had major bile leakage, which was treated conservatively without surgical or endoscopic intervention. Wound infection was seen in two patients in the T-tube group and one patient in the primary closure group. In follow up assessment, there was no intra-abdominal collection in both groups. Overall postoperative complications include biliary complications, wound infection and intraabdominal collections, were seen in four patients in the T-tube group and six patients in primary closure group; that was not statistically significant. Primary (Para) closure of CBD after open choledochotomy is feasible and is as safe as T-tube insertion. In effect, primary closure avoids T-tube insertion and disadvantages associated with the use of T-tube. Primary closure can be recommended for selected patients with choledocholithiasis. Medicine Today 2017 Vol.29(1): 15-18